Tingkat Perilaku Konsumtif Mahasiswa Universitas Negeri Padang - Muhammad Farhan (Dinasti Research, 2022)
Level of consumptive behavior of Padang State University students. The purpose of this study was to determine the level of active consumptive behavior of Padang State University students. This type of research uses quantitative techniques in the form of descriptive analysis. This study involved 54 UNP student respondents from various departments and batches using a purposive random sampling technique as a sampling step. The data analysis technique used in this study uses the IBM SPSS Statistics 26 application used as a categorization of research subjects. The results showed that the dominant level of consumptive behavior among UNP students was low, namely around 59.3%, the remaining 33.3% (moderate), and 7.4% (high).